Hit me hard and soft [compact disc] - Eilish, Billie, 2001-; Eilish, Billie, 2001-; Finneas, 1997- (Interscope Records, 2024)
Billie Eilish's third studio album is her most daring body of work to date; a diverse yet cohesive collection of songs, ideally listened to in its entirety from beginning to end. It does exactly as the album title suggests; hits you hard and soft both lyrically and sonically, while bending genres and defying trends along the way. With the help of her brother and sole collaborator, Finneas, the pair wrote, recorded, and produced the album together in their hometown of Los Angeles. This album comes on the heels of her two massively successful albums "When We All Fall Asleep Where Do We Go?" and "Happier Than Ever" and works to further develop the world of Billie Eilish.